A Line to Kill - Horwitz, Anthony (London Century, 2021)
"I couldn't see the sea from my bedroom but I could hear the waves breaking in the distance. They reminded me that I was on a tiny island. And I was trapped." There has never been a murder on Alderney. It's a tiny island, just three miles long and a mile and a half wide. The perfect location for a brand-new literary festival. Private Investigator Daniel Hawthorne has been invited to talk about his new book. The writer, Anthony Horowitz, travels with him. Very soon they discover that all is not as it should be. Alderney is in turmoil over a planned power line that will cut through it, desecrating a war cemetery and turning neighbour against neighbour. The visiting authors - including a blind medium, a French performance poet and a celebrity chef - seem to be harbouring any number of unpleasant secrets. When the festival's wealthy sponsor is found brutally killed, Alderney goes into lockdown and Hawthorne knows that he doesn't have to look too far for suspects. There's no escape. The killer is still on the island. And there's about to be a second death..
Detective and mystery stories